Autoimmune Congenital Complete Heart Block: How Late Can It Occur? - Luv Makadia; Peter Izmirly; Jill P. Buyon; Colin K. L. Phoon (Thieme Medical Publishers, Inc., 2023)
Objective Maternal anti-Ro (SSA) and/or anti-La (SSB) antibodies are a risk factor for congenital complete heart block (CHB). Because detailed analysis of the incidence of CHB after 24 weeks of gestational age (GA) is lacking, we aimed to ascertain the risk of "later-onset" CHB among offspring of SSA/SSB-positive mothers in the published literature. Study Design Using search terms "neonatal lupus heart block" and "autoimmune congenital heart block" on PubMed and Ovid, we gathered prospective studies of SSA/SSB-positive mothers with fetal echo surveillance starting from before CHB diagnosis and retrospective cases of fetal CHB diagnosis after 24 weeks of GA (if there was prior normal heart rate) or after birth. Results Ten prospective studies included 1,248 SSA/SSB-positive pregnancies with 24 cases of CHB diagnosed during pregnancy (1.9%). Among these, three (12.5%) were after 24 weeks-at weeks 25, 26, and 28. Our retrospective studies revealed 50 patients with CHB diagnosis in late fetal life and neonatal period and 34 in the nonneonatal childhood period. An additional four cases were diagnosed after age 18 years. Conclusion Later-onset autoimmune CHB in offspring of SSA/SSB-positive mothers does occur. Our analysis suggests that prenatal surveillance should continue beyond 24 weeks of GA but is limited by inconsistent published surveillance data.